A Novel FC116/BC10 Mutation Distinctively Causes Alteration in the Expression of the Genes for Cell Wall Polymer Synthesis in Rice - Zhang, Mingliang; Wei, Feng; Guo, Kai; Hu, Zhen; Li, Yuyang; Xie, Guosheng; Wang, Yanting; Cai, Xiwen; Peng, Liangcai; Wang, Lingqiang (Frontiers in Plant Science, 2016)
We report isolation and characterization of a fragile culm mutant fc116 that displays reduced mechanical strength caused by decreased cellulose content and altered cell wall structure in rice. Map-based cloning revealed that fc116 was a base substitution mutant (G to A) in a putative beta-1,6-N-acetylglucosaminyltransferase (C2GnT) gene (LOC_Os05g07790, allelic to BC10). This mutation resulted in one amino acid missing within a newly-identified protein motif “R, RXG, RA”. The FC116/BC10 gene was lowly but ubiquitously expressed in the all tissues examined across the whole life cycle of rice, and slightly down-regulated during secondary growth. This mutant also exhibited a significant increase in the content of hemicelluloses and lignins, as well as the content of pentoses (xylose and arabinose). But the content of hexoses (glucose, mannose and galactose) was decreased in both cellulosic and non-cellulosic (pectins and hemicelluloses) fractions of the mutant. Transcriptomic analysis indicated that the typical genes in the fc116 mutant were up-regulated corresponding to xylan biosynthesis, as well as lignin biosynthesis including p-hydroxyphenyl (H), syringyl (S) and guaiacyl (G). Our results indicate that FC116 has universal function in regulation of the cell wall polymers in rice.